Promoting Translational Research Among Movement Science, Occupational Science, and Occupational Therapy. Issue 1 (2nd January 2017) - Sainburg, Robert L.; Liew, Sook-Lei; Frey, Scott H.; Clark, Florence
ABSTRACT: Integration of research in the fields of neural control of movement and biomechanics (collectively referred to as movement science) with the field of human occupation directly benefits both areas of study. Specifically, incorporating many of the quantitative scientific methods and analyses employed in movement science can help accelerate the development of rehabilitation-relevant research in occupational therapy (OT) and occupational science (OS). Reciprocally, OT and OS, which focus on the performance of everyday activities (occupations) to promote health and well-being, provide theoretical frameworks to guide research on the performance of actions in the context of social, psychological, and environmental factors. Given both fields' mutual interest in the study of movement as it relates to health and disease, the authors posit that combining OS and OT theories and principles with the theories and methods in movement science may lead to new, impactful, and clinically relevant knowledge. The first step is to ensure that individuals with OS or OT backgrounds are academically prepared to pursue advanced study in movement science. In this article, the authors propose 2 strategies to address this need.